Chromogranin B is associated with impaired coronary collateralization and heart failure in patients with stable angina and chronic total occlusion. (25th November 2020) - Shen, Y; Wang, X.Q; Ding, F.H; Yang, Z.Q; Lu, L; Zhang, R.Y; Shen, W.F
Abstract: Background: Chromogranin B (CgB) is a member of granin family that can be cleaved into a number of bioactive peptides. Previous studies showed that CgB is produced in cardiomyocytes and is increased in heart failure animals and patients in proportion to disease severity. Chronic total occlusion (CTO) of coronary artery leads to sustained myocardial ischemia which predisposes to adverse cardiovascular outcomes including heart failure. Purpose: In this study, we sought to investigate the association between CgB and coronary collateralization formation and heart failure in patients with stable angina and CTO. Methods: A total of 720 subjects with stable angina and CTO of at least one major coronary artery were enrolled in this study. CgB was assayed using an ELISA kit and the degree of coronary collaterals supplying the distal aspect of a total occlusion from the contralateral vessel was graded according to Rentrop classification. Results: These was a stepwise decrease in levels of CgB with increasing Rentrop grades of coronary collateralization (P=0.001). Compared with the good collateralization (Rentrop grade 2–3) group, CgB was significantly higher in subjects with poor coronary collateralization (Rentrop grade 0–1; 1222.95 [IQR 506.24–2710.24] pg/mL vs. 776.17 [IQR 276.24–2209.39] pg/mL, P<0.001). Consistent results were found across subgroups of age, sex and the presence of diagnosed diabetes. In subjects with poor collateralization, CgB was positively correlated to N-terminal–pro-brain natriuretic peptide (NT-proBNP) levels (both log-transformed; Pearson's r=0.280, P=0.005). This correlation was markedly enhanced (Pearson's r=0.501, P<0.001) in the poorly-collateralized heart failure subgroup with left-ventricular ejection fraction (LVEF) <50%. Consistently, an inverse correlation was present between log-transformed CgB and LVEF (Pearson's r=−0.528, P<0.001) in the same subgroup. After adjusting for conventional confounding factors and LVEF, CgB remained significantly associated with impaired coronary collateralization (odds ratio: 1.314 [95% CI 1.097–1.590], P=0.004). Inclusion of CgB led to a better diagnostic accuracy as confirmed by net reclassification improvement (NRI) of 17.70% (95% CI 8.08–27.32%, P<0.001) and integrated discrimination improvement (IDI) of 1.98% (95% CI 0.63–3.34%, P=0.004). Conclusions: CgB is an independent predictor of poor coronary collateralization and is related to worse heart function in patients with stable angina and CTO. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Natural Science Foundation of China